Nonfouling Response of Hydrophilic Uncharged Polymers. (17th June 2013) - Serrano, Ângela; Sterner, Olof; Mieszkin, Sophie; Zürcher, Stefan; Tosatti, Samuele; Callow, Maureen E.; Callow, James A.; Spencer, Nicholas D.
Abstract Polymeric ultrathin films present a possible line of attack against marine biofouling for some applications. A protocol that provides a reliable comparison of the resistance of different polymers to biofouling is described. This is achieved through the use of a common, azide‐terminated adhesion monolayer, to which different nonfouling polymers of various molecular weights, specifically poly(ethylene glycol) (PEG), poly(2‐ethyl‐2‐oxazoline) (PEOXA), poly(vinyl pyrrolidone) (PVP), poly(vinyl alcohol) (PVA), and dextran are covalently bound. These functionalized surfaces are characterized by dynamic contact angle, ellipsometry, and X‐ray photoelectron spectroscopy (XPS). To validate the developed protocol and evaluate performance against a selection of well‐known, marine‐fouling organisms, the nonfouling surfaces are subjected to a comparative biological study by exposure to a complex protein solution (with characterization via ellipsometry and quartz crystal microbalance with dissipation (QCM‐D)), marine bacteria (Cobetia marina and Marinobacter hydrocarbonoclasticus), and zoospores of the green alga Ulva linza. The resulting data are used to draw conclusions on structure‐property relationships. Chemical resistance towards marine fouling can be achieved using the described immobilization method, but is highly dependent on the species tested. Findings show that PVP (55 kDa)‐coated surfaces display consistent resistance towards all tested solutions and organisms and, hence, this polymer could be considered as a potential material for marine‐nonfouling applications.